Threshold for endometrial sampling among postmenopausal patients without vaginal bleeding. Issue 3 (16th November 2015) - Louie, Michelle; Canavan, Timothy P.; Mansuria, Suketu
Abstract: Objective: To provide an optimum threshold for endometrial biopsy sampling among postmenopausal women without vaginal bleeding and an incidentally‐found endometrial lining of above 4 mm. Methods: A cohort of postmenopausal women (aged ≥ 50 years) who underwent pelvic ultrasonography at a tertiary US hospital for indications other than vaginal bleeding was retrospectively evaluated. Women were included if they had an endometrial lining of above 4 mm. Logistic regression was performed to determine the probability of endometrial carcinoma and atypical hyperplasia at each increasing millimeter of endometrial thickness from 4 to 20 mm. Results: Among 462 women, carcinoma was identified in 9 (1.9%) and atypical hyperplasia in 7 (1.5%). An endometrial thickness of or above 14 mm was significantly associated with atypical hyperplasia (odds ratio 4.29; 95% confidence interval 1.30–14.20; P = 0.02), with a negative predictive value of 98.3%. A thickness of or above 15 mm was associated with carcinoma (odds ratio 4.53; 95% confidence interval 1.20–17.20; P = 0.03), with a negative predictive value of 98.5% and a 0.06% risk of cancer. Conclusion: Irrespective of conventional risk factors, an incidentally‐found thickened endometrial lining of less than 15 mm might not warrant endometrial biopsy sampling among postmenopausal women without vaginal bleeding.